Achieving body confidence for young children: Development and pilot study of a universal teacher-led body image and weight stigma program for early primary school children. Issue 6 (2nd November 2018) - Damiano, Stephanie R.; Yager, Zali; McLean, Siân A.; Paxton, Susan J.
ABSTRACT: Negative body image attitudes develop in early childhood and there is a need for school-based resources during the early school years, but no teacher-delivered curriculum-based resources exist to mitigate these attitudes in young children. Achieving Body Confidence for Young Children (ABC-4-YC), a universal body dissatisfaction and weight stigma prevention program, was developed and then delivered in a pilot study. Fifty-one 5- to 8-year-old children completed pre- and post-intervention interviews assessing body image attitudes, and seven teachers provided feedback. Significant improvement in body esteem and positive teacher feedback were found. The results provide preliminary support for ABC-4-YC to improve children's body image attitudes, but extensive evaluation is needed.